Grandma's gift - Velasquez, Eric (New York Walker, 2010)
The author describes Christmas at his grandmother's apartment in Spanish Harlem the year she introduced him to the Metropolitan Museum of Art and Diego Velazquez's portrait of Juan de Pareja, which has had a profound and lasting effect on him.
Pura Belpre Award.
Keywords: Grandmothers -- Fiction; Christmas -- Fiction; Gifts -- Fiction; Artists -- Fiction; Puerto Ricans -- New York (State) -- New York -- Fiction; African Americans -- Fiction; New York (N.Y.) -- Fiction